Antimicrobial Activity and Metabolite Profiles of Begonia multangula Blume from Cibodas Botanical Garden and Gunung Halimun Salak National Park, Indonesia - Niken Pertiwi, Nyoman Ayu; Dewi Jumiarni; Muhammad Efendi; Intani Quara Lailaty (JSMARTech, 2025)
The resistance of microorganisms requires innovation in finding for alternative natural substances with antimicrobials properties. One of the plants reported to have antimicrobial potential is the plant Begonia multangula Blume. The purpose of this study was to examine the antimicrobial activity and metabolite profiles of ethanol extracts from the leaf and petiole of B. multangula originating from Cibodas Botanical Garden (KRC) and Gunung Halimun Salak National Park (TNGHS). Ethanol extracts of B. multangula leaf and petiole from KRC and TNGHS at a concentration of 100 mg/ml were tested for their antimicrobial activity against the growth of Staphylococcus aureus ATCC 25923 and Candida albicans using the disk diffusion method. Tetracycline 100 mg/ml and fluconazole 50 mg/ml were used as positive controls, and aquadest as a negative control. The metabolite profile compounds were obtained by GC-MS analysis. The results of the study showed that the highest antimicrobial activity was found in the leaf extract of B. multangula from KRC, with an average inhibition zone of 13,5 ± 1,73 mm against S. aureus and 10 ± 0,08 mm against C. albicans, which categorized as moderate. The most highly detected antimicrobial metabolites in the leaf and petiole extracts of B. multangula from KRC were Hexadecanoic acid ethyl ester. Furthermore, the major compound found in the B. multangula from TNGHS, was Neophytadiene and n-Hexadecanoic acid in leaf and petiole. These findings suggest that B. multangula has the potential to be developed as a natural antimicrobial agent in the future